Vector hysteresis loops of rare earth magnets measured in a biaxial vibrating sample magnetometer - G. Martinek; T. Gross; M. Lanz; G. Schneider; D. Goll (AIP Advances, 2024)
In many permanent magnet applications, there are regions in the magnet volume where the magnetic field acts at large angles to the direction of magnetization. The hysteresis curves, however, are determined almost exclusively with the magnetic fields applied along the preferred axis. This lack of information severely impairs the numerical modeling of important aspects of electrical machines, such as the risk of demagnetization or a reliable prediction whether a rotor can be assembled with unmagnetized magnets and subsequently magnetized in a multipole magnetizing fixture. In the rare cases where measurements with the field applied at an angle are performed, only the magnetization component in the direction of the applied field is detected. A reliable simulation would require measurements of the complete magnetization vector in fields applied at all angles. To this end, a commercially available vibrating sample magnetometer with a superconducting solenoid providing up to ±9 T was modified, replacing the existing detection coils with a twofold coil system measuring two orthogonal components of the magnetization. Details of this modification are reported, along with some examples of vectorial hysteresis curves measured on different types of rare earth magnets.